О сегментарном распределении почечных артерий у некоторых млекопитающих - Бурачинский, М.Т. (Вестник зоологии, 1978)
In kidneys of Erinaceus europaeus L., 3 rodent species, Felis domesticus L. and Ovis aries L. there are 2-3 ventral and 2-3 dorsal segmentary arteries. in Canis familiaris L. their number may reach 5. E. europaeus L., besides that, has one cranial and one caudal polar artery. In Cavia cobaya Marcgraf and O. aries L. instead of ventral and dorsal arteries there may be cranial and caudal ones. The same order of segmentary arteries distribution is observed in Sus scrofa domestica L., Bos taurus domesticus L. and Equus caballus domesticus L.